2019
DOI: 10.1038/s41396-019-0529-2
|View full text |Cite
|
Sign up to set email alerts
|

Host genetic effects upon the early gut microbiota in a bovine model with graduated spectrum of genetic variation

Abstract: Multiple synergistic factors affect the development and composition of mammalian gut microbiota, but effects of host genetics remain unclear. To illuminate the role of host genetics on gut microbiota, we employed animals with a graduated spectrum of genetic variation with minimal environmental influences. We bred 228 calves with linearly varying breed composition from 100% Angus (Bos taurus) to 100% Brahman (Bos indicus), as a proxy for genetic variation, and then raised the offspring in the same environment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 90 publications
(88 reference statements)
4
60
3
1
Order By: Relevance
“…In addition to antibiotic usage, the selection pressure during the process of evolution in microbial communities could be another reason for naturally occurring antibiotic resistant bacteria. Recent studies suggested that genomic breed composition of cattle was also associated with different gut microbiota structure (Fan et al, 2019a) that affects the colonization of antibiotic resistant bacteria (Fan et al, 2019b). In these cases, the prevalence of antibiotic resistant bacteria might not be directly correlated with antibiotic usage, and even farms without antibiotic supplementation contained ESBL and AmpC producing bacteria in both environmental and fecal samples (Mir et al, 2016(Mir et al, , 2018Teng et al, 2019), coinciding with the results of our study (Figures 1B,D).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to antibiotic usage, the selection pressure during the process of evolution in microbial communities could be another reason for naturally occurring antibiotic resistant bacteria. Recent studies suggested that genomic breed composition of cattle was also associated with different gut microbiota structure (Fan et al, 2019a) that affects the colonization of antibiotic resistant bacteria (Fan et al, 2019b). In these cases, the prevalence of antibiotic resistant bacteria might not be directly correlated with antibiotic usage, and even farms without antibiotic supplementation contained ESBL and AmpC producing bacteria in both environmental and fecal samples (Mir et al, 2016(Mir et al, , 2018Teng et al, 2019), coinciding with the results of our study (Figures 1B,D).…”
Section: Discussionsupporting
confidence: 89%
“…Human microbiota composition was frequently discovered to be collectively shaped by multiple host factors ( 46 , 47 ). For example, genetic variation in host protein NOD2 (HGF) and the immune response stimulated by the NF-kappa B pathway (HIF) could collectively increase the abundance of microbes in the Enterobacteriaceae family, and this microbiota dysbiosis had been discovered as a leading cause of neonatal meningitis ( 13 ).…”
Section: Factual Content and Data Retrievalmentioning
confidence: 99%
“…All in all, the GIMICA comprehensively provided the host genetic and immune factors that shape human microbiota (as illustrated in Figure 1 ), which allowed the collective considerations among the different types of factor (between HGF and HIF; between host and environmental factors). Since the composition of MCs should be considered as a complex shaped by the combination of both host and environmental factors ( 46–48 ), the GIMICA is expected to have implication for the future practice of MCs-related studies on human physiology and health ( 1–3 , 49–53 ).…”
Section: Introductionmentioning
confidence: 99%
“…Breast milk includes almost 10^9 bacterial cells/L and transfers healthy microbiota from mother to the child, which increase infant's immunity through competing with pathogens [9][10][11]. And then, this microbiomes gradually changes to adulthood microbiomes under influence of several factors such as the breed, the family ,geographic and socio-economic factors, diet and nutrition, nutritional supplements, exercises, medications like antibiotics, age, some pathological conditions like inflammatory disorders, diabetes, stress-related factors [12] and finally genetic factors, which play a crucial role in all stages of microbiota formation [13][14][15][16]. For example, a study on twins revealed an association between Bifid bacterium and the lactase (LCT) gene locus and also a correlation between the host gene ALDH1L1 and the bacteria SHA-98 [14].…”
Section: Introductionmentioning
confidence: 99%